$\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)$ are the coordinates of the two basis vectors, not the actual vectors .
So $\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)$ represents $\vec{e_1}$ and $\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)$ represents $\vec{e_2}$ .
In an orthonormal basis we have the dot product of basis vectors is zero : $\vec{e_1} \cdot \vec{e_2} =0$.
But in some other basis it might be that : $\vec{e'_1} \cdot \vec{e'_2} \neq 0$ even though the coordinates of the basis vectors are the same in both cases.
In other words : in the $\left\{ \vec{e'_1}, \vec{e'_2}\right\}$ basis , $\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right) \cdot \left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right) \neq 0 $ . In terms of coordinates you could say that this is because the matrix for the dot product is not : $\left(
\begin{array}{c , c}
1 & 0 \\
0 & 1 \\
\end{array}
\right)$ in that basis.
Update :
The question is about an inner product space and how it is affected by a change of basis.
As an example we first look at the normal 2-D Euclidean space with orthonormal basis. The basis vectors now are represented in coordinates by these two matrices:
$\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)$
The inner product is represented by this matrix : $\left(
\begin{array}{c , c}
1 & 0 \\
0 & 1 \\
\end{array}
\right)$ so that the inner product of $\left(
\begin{array}{c}
a \\
b \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
c \\
d \\
\end{array}
\right)$ becomes : $\left(
\begin{array}{c , c}
1 & 0 \\
0 & 1 \\
\end{array}
\right)\left(
\begin{array}{c}
a \\
b \\
\end{array}
\right)\left(
\begin{array}{c}
c \\
d \\
\end{array}
\right) = \left(
\begin{array}{c}
a & b\\
\end{array}
\right)\left(
\begin{array}{c}
c \\
d \\
\end{array}
\right)=ac+bd$
Now we express this same system with respect to a new basis : Let's say our new basis vectors become (expressed in terms of the old orthonormal basis vectors):
$\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
1 \\
1 \\
\end{array}
\right)$ . These are their coordinates with respect to the 'old' $\left\{ \vec{e_1}, \vec{e_2}\right\}$ basis .
But the SAME two new basis vectors expressed in terms of the new basis are of course :
$\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)$ , so these are their coordinates with respect to the new $\left\{ \vec{e'_1}, \vec{e'_2}\right\}$ basis . The old $\vec{e_1} , \vec{e_2} $ vectors with respect to the new coordinate system ($\left\{ \vec{e'_1}, \vec{e'_2}\right\}$) become: $\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)$ and $\left(
\begin{array}{c}
-1 \\
1 \\
\end{array}
\right)$
Changing the basis also means that coordinates of all other vectors and matrices in the old system need to be transformed to the new $\left\{ \vec{e'_1}, \vec{e'_2}\right\}$ system :
A : Old system $\left\{ \vec{e_1}, \vec{e_2}\right\}$ :
$\vec{e_1}=\vec{e'_1}$
$\vec{e_2}=\vec{e'_2}-\vec{e'_1}$
$\vec{a}= \left(
\begin{array}{c}
a_1 \\
a_2 \\
\end{array}
\right)$ , $\vec{b}= \left(
\begin{array}{c}
b_1 \\
b_2 \\
\end{array}
\right)$
The dot product : $\vec{a}\cdot\vec{b}=a_1b_1\vec{e_1}\cdot\vec{e_1}+a_2b_2\vec{e_2}\cdot\vec{e_2}$ $\enspace$ , $\enspace$ matrix form dot product : $\left(
\begin{array}{c , c}
1 & 0 \\
0 & 1 \\
\end{array}
\right)$
B : New system $\left\{ \vec{e'_1}, \vec{e'_2}\right\}$ :
$\vec{e'_1}=\vec{e_1}$
$\vec{e'_2}=\vec{e_1}+\vec{e_2}$
$\vec{a}= \left(
\begin{array}{c}
a_1' \\
a_2' \\
\end{array}
\right) = a_1\vec{e'_1} + a_2(\vec{e'_2}-\vec{e'_1}) \implies a_1'=a_1-a_2 \enspace , \enspace a_2' = a_2 $
$\vec{b}= \left(
\begin{array}{c}
b_1' \\
b_2' \\
\end{array}
\right) = b_1\vec{e'_1} + b_2(\vec{e'_2}-\vec{e'_1}) \implies b_1'=b_1-b_2 \enspace ,\enspace b_2' = b_2 $
The dot product : $\vec{a}\cdot\vec{b}=a_1b_1+a_2b_2=(a_1'+a_2')(b_1'+b_2')+a_2'b_2' =a_1'b_1'+a_1'b_2'+ a_2'b_1'+ 2a_2'b_2'= \left(
\begin{array}{c}
a_1'+a_2' & a_1'+2a_2' \\
\end{array}
\right)\left(
\begin{array}{c}
b_1' \\
b_2' \\
\end{array}
\right) \implies $
Transformed matrix for the dot product becomes : $\left(
\begin{array}{c , c}
1 & 1 \\
1 & 2 \\
\end{array}
\right)$
So in the new coordinates $\vec{e_1}\cdot\vec{e_2}$ is still zero : $\left(
\begin{array}{c , c}
1 & 1 \\
1 & 2 \\
\end{array}
\right)\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)\left(
\begin{array}{c}
-1 \\
1 \\
\end{array}
\right)=\left(
\begin{array}{c}
1 & 1 \\
\end{array}
\right)\left(
\begin{array}{c}
-1 \\
1 \\
\end{array}
\right) =0$
And $\vec{e_1'}\cdot\vec{e_2'}$ is : $\left(
\begin{array}{c , c}
1 & 1 \\
1 & 2 \\
\end{array}
\right)\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right)=\left(
\begin{array}{c}
1 & 1 \\
\end{array}
\right)\left(
\begin{array}{c}
0 \\
1 \\
\end{array}
\right) =1$
Compare this last result to $\vec{e_1'}\cdot\vec{e_2'}$ in the old system:
$\left(
\begin{array}{c , c}
1 & 0 \\
0 & 1 \\
\end{array}
\right)\left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right)\left(
\begin{array}{c}
1 \\
1 \\
\end{array}
\right)=\left(
\begin{array}{c}
1 & 0 \\
\end{array}
\right)\left(
\begin{array}{c}
1 \\
1 \\
\end{array}
\right) =1$
We conclude that when we transform the coordinates of the dot product matrix to the new basis $\left\{ \vec{e'_1}, \vec{e'_2}\right\} = \left\{ \left(
\begin{array}{c}
1 \\
0 \\
\end{array}
\right), \left(
\begin{array}{c}
1 \\
1 \\
\end{array}
\right)\right\}$ we get the new dot product coordinates : $\left(
\begin{array}{c , c}
1 & 1 \\
1 & 2 \\
\end{array}
\right)$ and the dot products of all vectors remain unchanged as they should .
Another way to calculate the coordinates for the transformed dot product matrix is realizing that the dot product consists of combinations of two 'row'-basisvectors.
Row vectors and column vectors :
$\vec{e_{i}}$ is column vector , $\vec{e^{i}}$ is row vector.
Column vectors and row vectors together form numbers :
$\vec{e^{i}}(\vec{e_{j}}) = \vec{e_{i}}(\vec{e^{j}}) = \vec{e'_{i}}(\vec{e'^{j}})=\vec{e'^{i}}(\vec{e'_{j}})=\delta_{ij}$ where $\delta_{ij}$ is the Kronecker delta. This combination of column and row vectors to form a number is NOT the dot product and it IS coordinate independent.
Because column and row vectors together must produce coordinate independent numbers we can derive their transformation properties :
$\vec{e^1}=a\vec{e'^1} +b\vec{e'^2}$
$\vec{e^2}=c\vec{e'^1} +d\vec{e'^2}$
$1=\vec{e^2}(\vec{e_2})=\vec{e^2}(\vec{e'_2}-\vec{e'_1}) = (c\vec{e'^1} +d\vec{e'^2})(\vec{e'_2}-\vec{e'_1}) =-c+d $
$1=\vec{e^1}(\vec{e_1})= \vec{e^1}(\vec{e'_1}) = (a\vec{e'^1} +b\vec{e'^2})(\vec{e'_1}) =a $
$0=\vec{e^2}(\vec{e_1})= \vec{e^2}(\vec{e'_1}) = (c\vec{e'^1} +d\vec{e'^2})(\vec{e'_1})=c $
$0=\vec{e^1}(\vec{e_2})= \vec{e^1}(\vec{e'_2}-\vec{e'_1}) = (a\vec{e'^1} +b\vec{e'^2})(\vec{e'_2}-\vec{e'_1}) =-a+b$
It follows that :
$\vec{e^1}= \vec{e'^1} + \vec{e'^2}$
$\vec{e^2}= \vec{e'^2}$
The dot product ($DP$) expressed in the old row-basisvectors is :
$DP=\vec{e^{1}}\otimes \vec{e^{1}}+\vec{e^{2}}\otimes \vec{e^{2}}$
In terms of the new basis vectors this becomes :
$DP=(\vec{e'^1} + \vec{e'^2})\otimes (\vec{e'^1} + \vec{e'^2})+\vec{e^{2}}\otimes \vec{e^{2}} \implies$
$DP= \vec{e'^1}\otimes \vec{e'^1} + \vec{e'^1}\otimes \vec{e'^2} +\vec{e'^2}\otimes \vec{e'^1} + 2\vec{e'^2}\otimes \vec{e'^2} = \left(
\begin{array}{c , c}
1 & 1 \\
1 & 2 \\
\end{array}
\right) $